Pengaruh Cycling Test Terhadap Mutu Fisik Sabun mandi Cair ekstrak Meniran Hijau (Phyllanthus Ninuri L) - Nor Latifah; Raudatul Patimah; Kurnia (JCPS (Journal of Current Pharmaceutical Sciences), 2025)
The skin can be cleansed and treated using soap. The most common bacteria found on the skin is Staphylococcus aureus, which can cause various skin problems. A natural ingredient known for its antibacterial properties is green Phyllanthus niruri leaves. To facilitate its application, it is necessary to develop it into a stable liquid soap formulation in terms of physical quality. The aim of this study was to determine the physical stability of a liquid soap formulation containing ethanol extract of green Phyllanthus niruri leaves, both before and after undergoing a cycling test on the best formulation.This research began with the processing of simplicia and extraction, followed by the formulation of liquid soap using green Phyllanthus niruri leaf extract with variations in KOH concentrations (14%, 16%, and 18%). The liquid soap formulations were then evaluated until the best formula was selected and subjected to a cycling test. Among the three formulas tested, the best formulation based on physical characteristics was F2, which used 16% KOH concentration. This formula was subsequently subjected to a cycling test for six cycles. The cycling test included organoleptic examination, homogeneity, pH, viscosity, foam height, and foam stability. The conclusion of this research on cycling tests shows that the physical quality of the preparation in the best formula, namely F2 (16%), showed significant changes in physical quality which was stable for 6 cycles.